A Comprehensive Analysis of Robot-Assisted Surgery Uptake in the Pediatric Surgical Discipline - Fernandez, Nicolas; Farhat, Walid A. (Frontiers in Surgery, 2019)
Introduction: Robotic assisted surgery (RAS) is one of the most recent surgical approaches that has quickly been adopted. Over the last decade, a vast amount of manuscripts has been published. The quality of published literature about this innovative technology remains supported by case-reports and retrospective case-series. Historical behaviour of literature productivity and implementation of laparoscopy followed a similar trend. We present a historical bibliometric comparison of the most cited manuscripts since laparoscopy and RAS were implemented. Materials and Methods: A systematic search and review of the literature was undertaken by the authors. Literature search was performed in OVID, PubMed, EMBASE, Scopus, Web of Science and Google Scholar. The search period included all publications between 1985 and June 2018. All languages were included. Data analysis for graphical representation was performed using VOSviewer version 1.6.8 and Impact Index Analysis was used to adjust the citations by the time since publication. Results: A total of 1014 titles were identified. After applying exclusion criteria, 200 papers were included for the RAS arm and 402 for the laparoscopic one. Case-series was the most common type of publication. Average citations for laparoscopic manuscripts was 23 (SD +/- 31) and for RAS was 20 (SD +/- 31.5). The impact index analysis showed an average of 95 (SD +/-167) for laparoscopic manuscripts vs 66 (SD 101+/-) for RAS. The laparoscopic manuscript with the highest citation count had 199 citations with an impact index of 12.1. And the RAS manuscript with the highest citation count had 280 citations and an impact index of 4.3. Conclusion: Literature productivity in pediatric laparoscopic and RAS has quickly grown. Level of evidence literature productivity has been similar for both technologies with more impact for RAS in the community, exponentially growing at a faster pace than how laparoscopy was sin introduction. Current graduating generations have had a significant exposure to RAS during their adult training and for this reason we believe RAS has remained a leading topic in the pediatric urology specialty. Future directives need to focus on increasing the level of evidence to support innovation and development of pediatric instruments.